PENGGUNAAN WORDWALL TERHADAP HASIL BELAJAR SISWA DALAM PEMBELAJARAN IPAS DI SEKOLAH DASAR - Riyadi Saputra; Wiwik Okta Susilawati, Sandra Febriyaningrum (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
The background of this study is the low student motivation and learning outcomes due to the lack of variation in media used during the learning process. This study aims to determine the effect of using the interactive learning media Wordwall on students' learning outcomes in the subject of Natural and Social Sciences (IPAS) for Grade IV at SDN 02 Koto Salak. Wordwall, as an interactive digital media, is considered capable of creating an engaging and enjoyable learning atmosphere for students.The method used in this study is quantitative with a quasi-experimental design. The research sample consisted of two classes: the experimental class, which used Wordwall, and the control class, which used conventional methods. Data were obtained through pre-tests and post-tests to measure improvements in learning outcomes. Data analysis using the t-test showed a significant difference between the experimental and control classes. The results of the study proved that the use of Wordwall had a positive effect on students' learning outcomes. Keywords: Wordwall Usage, Learning Outcomes, Cognitive, IPAS, Elementary School.